Body mass index increase in preschoolers with heterogeneous psychiatric diagnoses treated with risperidone. (September 2021) - Avrahami, Matan; Peskin, Miriam; Moore, Tyler; Drapisz, Adi; Taylor, Jerome; Segal-Gavish, Hadar; Balan-Moshe, Livia; Shachar, Issac; Levy, Tomer; Weizman, Abraham; Barzilay, Ran
Objective: Use of risperidone in preschool-aged children is growing, with rising concerns of adverse metabolic consequences. Longitudinal data on risperidone-related weight gain in preschoolers are scarce. We aimed to evaluate changes in body mass index (BMI) that are associated with risperidone treatment in preschoolers. Method: We analyzed naturalistic, longitudinal data on 141 preschool children (112 boys, 29 girls) receiving psychiatric care. Mean patient age at baseline was 5.0 years (SD=0.8) and average follow-up period was 1.3 years (SD=0.8), with >8 mean BMI measurements per patient. We studied the effect of risperidone exposure ( n =78) on age-and-sex-standardized BMI (BMI Z-score) implementing mixed models with random subject intercepts to account for repeated measures, covarying for multiple confounders including demographics, stimulant treatment and psychiatric diagnoses. We employed similar models to study dose and duration effects. Results: Risperidone treatment was significantly associated with an increase in BMI (effect size of exposure=0.45 SD (SE=0.06), t (949)=7.7, p <0.001) covarying for stimulant exposure and other confounders, independent of treatment indication. Females exhibited stronger effects (risperidone treatment × sex interaction t =2.32, p =0.02)). Risperidone daily dose was associated with increase in BMI (for each additional 1 mg, effect size=0.28 SD (SE=0.07), t (419)=3.76, p <0.001). Conclusion: Similar to older populations, risperidone treatment in preschoolers is associated with significant weight gain, with evidence for dose effects. Findings provide critical data that can inform clinicians.